HUBUNGAN ANTARA JENIS PAKAN DENGAN LEBAH MADU DI TAMAN HUTAN RAYA GUNUNG TUMPA H.V. WORANG - Peni Beanal; Terry M. Frans; Reynold P. Kainde (Universitas Sam Ratulangi, 2021)
ABSTRACTThis study aims to determine the relationship between types of feed and types of honeybees in the area of Gunung Tumpa H.V. Forest Park. Worang. The research was conducted inSeptember 2020 in the Gunung Tumpa H.V. Forest Park area. Worang. This research usespurposive sampling method. The results showed 6 (six) types of honey bees, namely Apisdorsata, Apis mellifera, Apis cerana, Apis trigona, Bombus affinis, and Bombus terestris and 18(eighteen) types of plants (forage), namely Tembelekan (Lantana camara), Banyan tree (Ficusbenjamina), African Tulip Tree (Spathodea campulata), Sirihan forest / Sentok (Piper aduncumL) Mara tree (Macaranga hispida), Aren (Arenga pinnata), Candlenut (Aleurites moluccana),Buni (Anttidesma bunius) , Take / kulawi (Arenga undu latifolia), Kenanga (Cananga odorata),Rao (Dracontomelon dao), Melinjo (Gnetum gnemon), Bugis wood (Koordersiodendronpinnatum), Lamtoro (Leucaena leucocephala), Sengon (Albizia falcataria), Manga (Mango sp),Tremam (Trema orientalis), and Guava (Syzigium sp). The most common types of honey beesare Apis dorsata and Apis melifera and the most visited species of honey bees are Aren (Arengapinnata) and Tembelekan (Lantara camara).Keywords: Relationship, Type of Feed, Types of Honey Bees, Mount Tumpa